Comprehensive periodontal/orthodontic treatment of bimaxillary dentoalveolar protrusion caused by posterior bite collapse due to periodontal disease - Konno Masahiro; Iijima Masahiro; Kado Takashi; Furuichi Yasushi; Mizoguchi Itaru (Sciendo, 2017)
Increased mobility of teeth in adult patients with advanced periodontal disease causes posterior bite collapse, which is characterised by mesial inclination of the molars and vertical dimension loss, often resulting in bimaxillary dentoalveolar protrusion.